2015
DOI: 10.1002/bip.22639
|View full text |Cite
|
Sign up to set email alerts
|

Protein design: Past, present, and future

Abstract: Building on the pioneering work of Ho and DeGrado (J Am Chem Soc 1987, 109, 6751–6758) in the late 1980s, protein design approaches have revealed many fundamental features of protein structure and stability. We are now in the era that the early work presaged – the design of new proteins with practical applications and uses. Here we briefly survey some past milestones in protein design, in addition to highlighting recent progress and future aspirations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 114 publications
0
31
0
Order By: Relevance
“…The protein core has long been known to determine protein stability and provide the driving force for folding. [37][38][39][40][41][42][43][44][45] Additionally, in our previous work, we have found that several features of core packing are universal among well-folded experimental structures, such as the repacking predictability of core residue side chain placement, core packing fraction, and distribution of core void space. [46][47][48][49][50][51] This work suggests that analysis of core residue placement and packing in proteins more generally should be effective in determining the accuracy of protein decoys.…”
Section: Introductionmentioning
confidence: 87%
“…The protein core has long been known to determine protein stability and provide the driving force for folding. [37][38][39][40][41][42][43][44][45] Additionally, in our previous work, we have found that several features of core packing are universal among well-folded experimental structures, such as the repacking predictability of core residue side chain placement, core packing fraction, and distribution of core void space. [46][47][48][49][50][51] This work suggests that analysis of core residue placement and packing in proteins more generally should be effective in determining the accuracy of protein decoys.…”
Section: Introductionmentioning
confidence: 87%
“…Advancements introduced over the years by these and other researchers have aimed to improve the treatment of a range of physical effects towards a more realistic representation of proteins, including modeling backbone flexibility (9), better accounting for side-chain degrees of freedom (10,11), treatment of bulk-solvation and individual-water effects (12)(13)(14), consideration of ensemble properties of structure (15)(16)(17)(18), scoring function improvements (3,19), modeling the unfolded state (15,20,21), and others. Several recent reviews provide excellent summaries of achievements and challenges in CPD, including by Donald and co-workers (22) (a thorough analysis of algorithmic aspects), by Ilan Samish and Regan et al (23,24) (placing current work in a historical perspective), and Woolfson et al (25) (a commentary on the implications of the ability to design novel structures). Nevertheless, despite all of these developments, and many examples of successful designs in the literature (18,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), it is still the case that CPD methods are not robust.…”
Section: Introductionmentioning
confidence: 99%
“…11 As such, four-helix bundles have become key targets and scaffolds for de novo protein design. [12][13][14][15][16][17][18] Usually, these comprise amphipathic a helices. These helices assemble via their hydrophobic faces to form bundles with the hydrophobic side chains buried in a consolidated core.…”
Section: Introductionmentioning
confidence: 99%